Determinants of dividend policy in Sri Lanka: the panel data analysis / Lingesiya Kengatharan - Kengatharan, Lingesiya (Universiti Teknologi MARA, 2021)
The study aimed to emphasize the determinants of dividend policy in Sri Lankan firms. This study was conducted with 80 non - financial companies which were listed on Colombo Stock Exchange (CSE). The empirical research was focused on panel data analysis, and data was collected from annual reports for a five year period from 2013 to 2017. This study explored selected factors that influence dividend policy, including sales growth, leverage, firm size, profitability, EPS, liquidity, and risk. The panel data analysis employed pooled OLS, fixed - effect, and random - effect models. Based on the analysis, the fixed - effect model was thought to be the best fit for studying the factors that affect dividend policy. According to the outcome of fixed-effect model, among the seven input variables considered in this study, profitability, EPS, and risk were negatively linked to dividend policy. However, no significant relationship was found between dividend policy and sales growth, leverage, firm size, or liquidity. The findings contribute to the understanding that three parameters namely: profitability, EPS, and risk have been recognized as factors affecting dividend payouts in CSE’s listed companies. Hence, policymakers will be able to concentrate on the factors that influence shareholder wealth maximization.